Anti-counterfeiting strategy based on rare earths and biopolymers - Pereira, Daniela Vassalo [UNESP]; Mello, Yan Gorski [UNESP]; da Silva Barud, Hernane; Cavicchioli, Maurício; Ribeiro, Sidney José Lima [UNESP] (My University, 2022)
Commodity counterfeiting can be resolved by attaching labels made from biopolymers and down- and up-converting particles. Measurements of luminescence spectrum and SEM were made, proving the formation of particles and luminescence.